2016
DOI: 10.1089/pho.2015.4005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of High-Intensity Laser Therapy in Subacromial Impingement Syndrome

Abstract: HILT was found to be effective in the short term in the treatment of pain and disability in patients with SAIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…Karaca 13 analysed a series of 42 cases, the effect seen by Karaca lengthens one month more in this study, but this effect was not better than placebo. Santamato et al 15 reported finding better results in the high-intensity group than in the ultrasound group.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Karaca 13 analysed a series of 42 cases, the effect seen by Karaca lengthens one month more in this study, but this effect was not better than placebo. Santamato et al 15 reported finding better results in the high-intensity group than in the ultrasound group.…”
Section: Discussionmentioning
confidence: 67%
“…We applied the premise that for any given wavelength, the higher the power, the greater the ensuing penetration effects and the less the dispersion of energy. Even though Karaca 13 used a similar protocol to this study, with two phases per session, they used less power than we did (8 and 7 W, respectively). Other studies used a three-phase protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings with HILT (versus LLLT) were also confirmed in a study by Alayat et al 120 in patients with Bell’s palsy. HILT was also effective in the short-term management of pain and disability related to subacromial impingement syndrome, frozen shoulder and lateral epicondylitis 121 123 . HILT at wavelengths of 830 and 1,064 nm was better than TENS in improving control of pain and paresthesias secondary to carpal tunnel syndrome 124 .…”
Section: Laser Therapymentioning
confidence: 99%